Pemanfaatan Aplikasi SPAI untuk Mahasiswa Asing dalam Pembelajaran Bahasa Indonesia - Syihaabul Hudaa (Jurnal Bahasa Indonesia bagi Penutur Asing, 2021)
Mastery of vocabulary in Indonesian properly and correctly is not an easy thing. This problem is often conveyed by Indonesian language learners for foreign speakers (BIPA) at the Syarif Hidayatullah State Islamic University Jakarta. The purpose of writing this article is to convey the use of the SPAI application carried out by foreign students to obtain the definition of a foreign word and find the right word equivalent in Indonesian. This research belongs to the type of descriptive qualitative research using the online direct action research approach using zoom. The use of zoom was used because of the pandemic that made face-to-face classes impossible. Based on the research conducted, the researcher found that the SPAI application was very effective in using foreign students in finding the equivalent of a word in Indonesian.